NO EFFECT OF DIFFERENT ESTROGEN RECEPTOR LIGANDS ON COGNITION IN ADULT FEMALE MONKEYS - Lacreuse, Agnès (2008)
Many studies in women and animal models suggest that estrogens affect cognitive function. Yet, the mechanisms by which estrogens may impact cognition remain unclear. The goal of the present study was to assess the effects of different estrogen receptor (ER) ligands on cognitive function in adult ovariectomized female rhesus monkeys. The monkeys were tested for 6 weeks on a battery of memory and attentional tasks administered on a touchscreen: the object, face, and spatial versions of the Delayed Recognition Span Test (DRST) and a Visual Search task. Following a 2-week baseline period with oil vehicle treatment, monkeys were randomly assigned to one of 3 treatment groups: estradiol benzoate (EB), selective ERβ agonist (diarylpropionitrile DPN) or selective ER modulator tamoxifen (TAM). In each treatment group, monkeys received oil vehicle for 2 weeks and the drug for 2 weeks, in a cross-over design. After a 4-week washout, a subset of monkeys was re-tested on the battery when treated with a selective ERα agonist (propyl-pyrazole-triol, PPT) or oil vehicle. Overall, drug treatments had no or negligible effects on cognitive performance. These results support the contention that exogenous estrogens and selective estrogen receptor modulators (SERMS) do not significantly affect cognition in young adult female macaques. Additional studies are needed to determine whether the cognitive effects of estrogens in monkeys of more advanced age are mediated by ERβ, ERα or complex interactions between the two receptors.